An investigation of production and properties of RHA reinforced hybrid composites by vacuum infiltration method - Tanaay, Naci Arda; Okur, Onur; Duran, Osman; Yilmaz, Erkan; Turkumen, Mustafa; Mohamed Ariff, Azmah Hanim; Dele-Afolabi, Temitope Theophilus; Calin, Recep (IJERD, 2021)
The harmful effect of agricultural waste has been intensified over the last decade and impacts the environment every passing day. Rice husk waste is a major problem in Turkey and the far east countries. Due to the economic dependence of the mass cultivation and the production of rice, the disposal of the waste appears both time and money consuming. Alternative methods sought over the years and the implementation of the rice husk in the production of composites is seen as a promising method. RHA is a burning residue of rice husk and the implementation of RHA in the production of aluminum composites gained attention in recent years. In this study, aluminum composites having 5 wt.% Al2O3 reinforcement and 5 wt.% Al2O3/0.5, 1.0, and 1.5 wt.% RHA reinforcement were produced by vacuum infiltration process which is a cheap and cost-effective route. AA7075 alloy without any reinforcement was produced for comparison. Solution heat treatment at 480 °C for 2 hours was applied and then quenched following by aging heat treatment at 120 °C for 8 hours. The microstructure, microhardness, and wear tests of all composites were investigated. Increasing RHA content up to 1 wt.% and aging heat treatment increased the hardness of composites. Abrasion coefficient decreased by increasing RHA content.